A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF MTS DAARUN NAHDHAH THAWALIB BANGKINANG IN COMPREHENDING RECOUNT TEXTS - Sari, Rifqo Yuli; Delfi, Syofia; Aruan, Rumiri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This descriptive research was aimed to find out the ability of the second year students of MTs Daarun Nahdhah Thawalib Bangkinang in comprehending recount texts. The research data were collected in November 2016. The subject of this research was class VIII-A which consisted of 31 students. The data were collected by giving a test to the students in the form of multiple choice test. The test contained 40 items. Based on the research, it was found out that first: the ability of the second year students in reading comprehension is in good level with the mean score of 63.71. Second, the students? mean score in finding the main idea is in good level with the mean score of 63.87, finding the factual information in event is in good level with the mean score of 70.97, finding the factual information in re-orientation is in good level with the mean score of 70.32, in finding the meaning of vocabulary is in average level with the mean score of 58.39, in finding references is in good level with the mean score of 63.23, in finding inference is in good level with the mean score of 63.23, in finding social function is in good level with the mean score of 61.29. As a conclusion, the highest score obtained by the students is in finding factual information in event with the mean score of 70.97 which is categorized into good level, and the lowest score that the students got is in finding the meaning of vocabulary, with the mean score of 58.39 which is categorized into average level. It is recommended that the students must do more practice and read books to improve reading skills, especially in finding meaning of vocabulary, because the students got the lowest score in that term. Next, English teachers are recommended that be more creative and use or apply any strategies to teach the reading strategies that can be used in answering reading comprehension questions. The last, other researchers are recommended that conduct this research in other skills.Keywords: Students? Ability, Reading Comprehension, Recount Texts